Plasmodium berghei sporozoite challenge of vaccinated BALB/c mice leads to the induction of humoral immunity and improved function of CD8+ memory T cells. Issue 3 (18th January 2013) - Tartz, Susanne; Deschermeier, Christina; Retzlaff, Silke; Heussler, Volker; Sebo, Peter; Fleischer, Bernhard; Jacobs, Thomas
<x xml:space="preserve">Abstract</x> Protection against malaria can be achieved by induction of a strong CD8+ T‐cell response against the Plasmodium circumsporozoite protein (CSP), but most subunit vaccines suffer from insufficient memory responses. In the present study, we analyzed the impact of postimmunization sporozoite challenge on the development of long‐lasting immunity. BALB/c mice were immunized by a heterologous prime/boost regimen against Plasmodium berghei CSP that induces a strong CD8+ T‐cell response and sterile protection, which is short‐lived. Here, we show that protective immunity is prolonged by a sporozoite challenge after immunization. Repeated challenges induced sporozoite‐specific antibodies that showed protective capacity. The numbers of CSP‐specific CD8+ T cells were not substantially enhanced by sporozoite infections; however, CSP‐specific memory CD8+ T cells of challenged mice displayed a higher cytotoxic activity than memory T cells of immunized‐only mice. CD4+ T cells contributed to protection as well; but CD8+ memory T cells were found to be the central mediator of sterile protection. Based on these data, we suggest that prolonged protective immunity observed after immunization and infection is composed of different antiparasitic mechanisms including CD8+ effector‐memory T cells with increased cytotoxic activity as well as CD4+ memory T cells and neutralizing antibodies.